Exploring the misfolding and self-assembly mechanism of TTR (105–115) peptides by all-atom molecular dynamics simulation - Zhang, Yuqi; Zhu, Yanyan; Yue, Haiyan; Zhao, Qingjie; Li, Huiyu (Frontiers in Molecular Biosciences, 2022)
Pathological aggregation of essentially dissociative Transthyretin (TTR) monomers protein, driven by misfolded and self-interaction, is connected with Amyloid Transthyretin amyloidosis (ATTR) disease. The TTR monomers protein contains several fragments that tend to self-aggregate, such as residue 105-115 sequence (TTR (105-115)). However, the misfolding and aggregation mechanisms of TTR are still unknown. In this study, we explore the misfolding and self-assembly of TTR (105-115) peptides by all-atom molecular dynamics simulation. Our results indicate that the TTR (105-115) dimers appear dynamic performance and frequent conformational conversion without stable structures. In the tetramerization and hexamerization simulations, the results are reversed. When the number of peptides increases, the probability and the length of β-sheet contents increase. The β-barrels are recognized as the intermediates between random coil and fibrils. Our results show that that tetramers and hexamers both can form β-barrel intermediates and then aggregate into fibers. The critical nucleation for the formation of fibril should be larger than tetramer. The interactions between hydrophobic residues I107-L111 play an important role in the formation of stable fibrils at an early stage. Our results, which involved in the structural ensembles and early aggregation dynamics of TTR (105-115), will be useful to comprehend the nucleation and fibrillization of TTR.